Pengaruh Reliability, Responsiveness, Assurance, Empathy, dan Tangibles terhadap Daya Saing PT Samudera Sriwijaya Logistik - Kurnia, Wawan; Wadud, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The logistics service industry plays a crucial role in national and international economic development, driven by rapid growth in e-commerce and global trade. However, intense competition and rising demands for efficiency and innovation require companies to enhance their competitiveness through improved service quality, including reliability, responsiveness, assurance, empathy, and tangibles. This study analyzes the impact of service quality on the competitiveness of PT Samudera Sriwijaya Logistik using a quantitative approach with multiple regression analysis. Data were collected from 50 respondents through Proportionate Stratified Random Sampling. Validity, reliability, and classical assumption tests ensured model accuracy, while hypothesis testing employed the Goodness of Fit test, F-test, and t-test. Findings indicate that service reliability has the most significant impact on competitiveness, followed by tangibles, empathy, responsiveness, and assurance. Regression analysis shows that reliable and responsive services, supported by adequate facilities, enhance customer trust and satisfaction. The company has implemented policies such as delivery SOPs, service quality standards, and employee training to strengthen its competitive position. By prioritizing reliability, tangible assets, and customer-focused strategies, PT Samudera Sriwijaya Logistik can maintain its standing as a leading logistics service provider in a highly competitive industry.